2001
DOI: 10.1143/jjap.40.l97
|View full text |Cite
|
Sign up to set email alerts
|

Current Paths over Grain Boundaries in Polycrystalline Silicon Films

Abstract: An optoelectronic system is described for making quasi-simultaneous recordings of muscle transparency at orthogonal beam polarisations. A Pockels cell is used to oscillate the €-vector of a laser beam ( j . = 632.8, 514.5, 488 and 457.9 nm) through n12 radians (at 7.4 kHz), between 0 and 90 relative to the muscle long axis. The intensity of light transmitted by the muscle is detected using a photomultiplier tube. The photomultiplier output is fed to a sample-hold device which generates two analogue signals, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…On the other hand, an electric current may traverse grain boundary in a less-cross-section-area, more perpendicularpath manner to ensure that an electric current passes through the lower electrical-resistivity paths as possible as it can. These results are also consistent with the analysis by Kimura et al 3) which concluded that the current tends to flow over grain boundary perpendicularly and avoid passing through grain boundary triple junction. Since the two grain boundaries through which a fusion path crosses to adjacent grains are usually nonparallel, geometrical constraint of normal intersection requires the fusion path to be curved inside the grain.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, an electric current may traverse grain boundary in a less-cross-section-area, more perpendicularpath manner to ensure that an electric current passes through the lower electrical-resistivity paths as possible as it can. These results are also consistent with the analysis by Kimura et al 3) which concluded that the current tends to flow over grain boundary perpendicularly and avoid passing through grain boundary triple junction. Since the two grain boundaries through which a fusion path crosses to adjacent grains are usually nonparallel, geometrical constraint of normal intersection requires the fusion path to be curved inside the grain.…”
Section: Resultssupporting
confidence: 92%
“…In a two-dimensional simulation of silicon thin film taking grain boundaries as the trapping site of charge carriers, Kimura et al 3) have concluded that the current density is the highest in the center region of a grain. This phenomenon of non-uniform current distribution is more pronounced when the grain size is getting smaller (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Here, I flows through zigzag paths to avoid the high potential barriers at the triple points of the grain boundaries. 22,23 In other words, V H has an offset voltage because the Hall terminals are not electrically located just at the center of the zigzag paths, although they are spatially located just at the center of the current terminals. For example, the maximum offset voltage of 590 V in cell A corresponds to the difference between the electrical and structural centers of 240 nm because L = 40 m and V = 0.1 V. Therefore, the offset voltage is mainly caused not by the pattern variation but by the zigzag path.…”
Section: Discussionmentioning
confidence: 99%
“…The first assumption is that current paths flow perpendicular to the grain boundaries, and the validity has been confirmed elsewhere. 63) The second assumption is that the number of grain boundaries in a device can be known, and it can be determined as follows. The average grain size is observed using techniques such as scanning electron microscopy and tunneling electron microscopy, and the average number of grain boundaries is acquired.…”
Section: Discussionmentioning
confidence: 99%